Mild oxidation of Xiaolongtan lignite in aqueous hydrogen peroxide–acetic anhydride. (15th February 2015) - Liu, Jing; Wei, Xian-Yong; Wang, Yu-Gao; Zhang, Dong-Dong; Wang, Tie-Min; Lv, Jing-Hui; Gui, Juan; Qu, Meng; Zong, Zhi-Min
Highlights: Conditions for Xiaolongtan lignite (XL) oxidation with AHPO–AAH were optimized. Malonic acid and succinic acid dominated in the oxidation products. –CH2 – and –CH2 CH2 – are dominant bridged linkages connecting aromatic rings in XL. Abstract: Xiaolongtan lignite (XL) was subjected to the mild oxidation with aqueous hydrogen peroxide–acetic anhydride (AAH) under different conditions, including temperature, the amount of AAH, and time. Each reaction mixture was separated by filtration and subsequent treatments, including extraction with ethyl acetate (EA), to afford the EA-extractable portion (EAEP), which was analyzed with a gas chromatograph/mass spectrometer. The optimal conditions were determined to be 2 mL AAH, 50 °C, and 9 h for the oxidation of 0.1 g XL, based on the yields and product distributions of the EAEPs. In total, 47 carboxylic acids (CAs) were detected in the EAEPs under optimized conditions and aliphatic acids are the predominant species. Malonic and succinic acids account for more than 41% of all the CAs, suggesting that dominant linkages connecting aromatic rings (ARs) are –CH2 – and –CH2 CH2 – along with less amounts of polymethylene linkages such as –(CH2 ) n – ( n  = 3–7). Meanwhile, naphthalenecarboxylic acids and aliphatic linkages connecting three ARs are speculated to exist in XL. The investigation provides an effective approach for understanding the structural features of lignites and obtaining aliphatic acids, especially malonic and succinic acids.